2016
DOI: 10.1175/jas-d-14-0355.1
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Small-Scale Atmospheric Vortices via Horizontal Shearing Instability

Abstract: Motivated by high-resolution observations of small-scale atmospheric vortices along near-surface boundaries, this study presents a series of idealized simulations that attempt to replicate shear zones typical of drylines and other near-surface boundaries. The series of dry, constant potential temperature simulations are initialized with a north–south-oriented constant-vorticity shear zone and north–south periodic boundary conditions. In all simulations, the shear zones develop wavelike perturbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 81 publications
5
13
0
Order By: Relevance
“…A wind shear region with small perturbation grows to an observable wave-like pattern in 5−10 minutes, resulting in the rapid formation of elliptically-shaped vortices. We also find a rapid morphological change of vortex from circular to elliptical shapes, in good agreement with numerical simulations by Buban and Ziegler (2016).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A wind shear region with small perturbation grows to an observable wave-like pattern in 5−10 minutes, resulting in the rapid formation of elliptically-shaped vortices. We also find a rapid morphological change of vortex from circular to elliptical shapes, in good agreement with numerical simulations by Buban and Ziegler (2016).…”
Section: Discussionsupporting
confidence: 89%
“…Recent theoretical calculations by Buban and Ziegler (2016) have examined a temporal change of horizontal shear zone. A wind shear region with small perturbation grows to an observable wave-like pattern in 5−10 minutes, resulting in the rapid formation of elliptically-shaped vortices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trapp and Weisman (2003) argue that the mesovortices are produced by the tilting of crosswise baroclinic vorticity, which may be produced by the presence of a rear inflow jet (RIJ) in mature QLCS systems. Buban and Ziegler (2016) performed a series of numerical simulations that demonstrated that horizontal shearing instability (HSI) can produce miso-vortices (1 to 4 km) along baroclinic shear lines, with growth rates dependent on shear zone width and horizontal shear strength. Miso-vortices produced via HSI can grow into the low-level mesovortices that precede tornadogenesis.…”
Section: Introductionmentioning
confidence: 99%